Self-radiation force on a moving monopolar source. (10th December 2022) - Roux, A.; Martischang, J.-P.; Baudoin, M.
Abstract: Abstract : The radiation force exerted on an object by an acoustic wave is a widely studied phenomenon since the early work of Rayleigh, Langevin and Brillouin, and has led in the last decade to tremendous developments for acoustic micromanipulation. Despite extensive work on this phenomenon, the expressions of the acoustic radiation force applied on a particle have so far been derived only for a steady particle, hence neglecting the effect of its displacement on the radiated wave. In this work, we study the acoustic radiation force exerted on a monopolar source translating at a constant velocity that is small compared to the sound speed. We demonstrate that the asymmetry of the emitted field resulting from the Doppler effect induces a radiation force on the source opposite to its motion.